Back in School : How Student Parents Are Transforming College and Family - Pearson, A. Fiona (Book collections on Project MUSE., 2019)
"Back in School explores what it means to be a successful student and how these valuations are shaped by access to resources and cultural beliefs regarding the perceived purpose of a college education as we venture forward into the twenty-first century. These student parents have chosen to be a part of a traditional campus culture, attending public colleges and universities where they can learn, grow, and prepare themselves for not just a job but a life outside of school and work. In challenging dominant paradigms regarding the purpose and function of public higher education in the twenty-first century, these students are also, albeit not always consciously, calling for changes in that will produce greater socioeconomic and gender equity in our culture, on college campuses, and in their personal lives"--